PENENTUAN KRITERIA PENGHENTIAN ITERASI PADA ALGORITMA STROBERI - Mutia Nur Estri; Siti Rahmah Nurshiami; Rina Reorita; Muhammad Okky Ibrohim (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2018)
This paper discusses the application of two types of stopping criterion on the strawberry algorithm, which are stopping criteria based on iterative error and Cauchy criterion. Furthermore, the strawberry algorithm program is simulated on the optimization problem with the objective function is quadratic function. The simulation results on optimization problem with the objective function is quadratic function show that strawberry algorithm with stopping criterion based on Cauchy criterion has the best performance, when compared with stopping criterion based on iterative error and without stopping criterion